High-toughness tensile wear-resistant fabric and preparation method thereof
By using polylactic and bamboo fiber fabrics and applying specific wear-resistant agents to the surface, the problem of insufficient wear resistance of existing fabrics is solved, and the wear resistance and service life of the fabric is significantly improved.
Patent Information
- Application Number
- CN202411780937.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-28
AI Technical Summary
Existing textile fabrics have shortcomings in wear resistance and toughness, especially in workshop and construction site operations, which can easily lead to accelerated wear of clothes.
A fabric woven with polylactic and bamboo fibers is coated with an abrasion resistant agent including polytetrafluoroethylene, nanoboronitride, alcohol esters, organic polyether esters, fluorin surfactants and deionized water.
It improves the wear resistance and adhesion of the fabric and extends the service life of the fabric.
Smart Images

Figure CN119711201A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of fabrics, and in particular to a high-toughness, tensile-resistant, and wear-resistant fabric and a preparation method thereof. Background Art
[0002] Fabrics are materials used to make clothes. There are many types of fabrics, and most of the fabrics used to make clothes have the characteristics of being comfortable to wear, sweat-absorbent and breathable.
[0003] Wear resistance and toughness are very important for clothing fabrics, and this is the weak link of existing textile fabrics. Take common cotton fabrics as an example. Although cotton fabrics have good air permeability and warmth retention, they have poor wear resistance. When cotton fabrics are used in workshop operations and construction sites, the clothes are often rubbed against hard and rough objects, which can easily reduce the service life of the clothes. Summary of the invention In order to improve the wear resistance of fabrics, the present application provides a high-toughness tensile wear-resistant fabric and a preparation method thereof.
[0005] In the first aspect, the present application provides a high-toughness tensile wear-resistant fabric, which adopts the following technical solution: A high-toughness, tensile-resistant and wear-resistant fabric comprises a fabric body, wherein the fabric body is woven from polylactic acid fiber and bamboo fiber, and the surface of the fabric body is covered with a wear-resistant layer, wherein the wear-resistant layer is obtained by coating a wear-resistant agent on the surface of the fabric body, and the wear-resistant agent comprises 42-48 parts of polytetrafluoroethylene, 7-11 parts of nano boron nitride, 1.4-2.8 parts of alcohol ester dodecanedione, 1.2-1.8 parts of organic polyether ester, 0.6-0.8 parts of fluorine surfactant and 8-12 parts of deionized water.
[0006] By adopting the above technical solution, the wear-resistant agent produced by using polytetrafluoroethylene and nano boron nitride as main raw materials is coated on the surface of the fabric body, so that the fabric body has excellent wear resistance.
[0007] The fabric woven from polylactic acid fiber and bamboo fiber has high toughness and tensile resistance.
[0008] Adding nano boron nitride to the wear-resistant agent can, on the one hand, increase the gap of the wear-resistant coating and make the wear-resistant coating denser. On the other hand, nano boron nitride has a good lubricating effect. At the same time, when the surface of the fabric produces wear resistance, nano boron nitride will form a dense transfer film on the surface of the fabric, thereby improving the wear resistance of the wear-resistant layer.
[0009] In addition, nano boron nitride will directly increase the contact area with its extremely small particle size, and nano particles have good thixotropic properties, thereby improving the adhesion of the wear-resistant layer on the surface of the fabric body.
[0010] In addition, organic polyether esters have the properties of incompatibility and low surface tension, which can reduce the generation of foam, thereby reducing the presence of pores in the coating and effectively improving the stability of the coating.
[0011] Fluorine surfactants can promote the reduction of the surface tension of the system and improve the compatibility of the organic polyether ester with the system, thereby improving the adhesion of the wear-resistant layer on the surface of the fabric body.
[0012] Preferably, the nano boron nitride is prepared by modification, and the modification preparation method of the nano boron nitride comprises the following steps: The nano boron nitride and polyimide are mixed and stirred evenly to obtain modified boron nitride.
[0013] By adopting the above technical scheme, nano-boron nitride and polyimide are connected by chemical bonds, thereby enhancing the interface affinity and compatibility of nano-boron nitride and polyimide, thereby improving the dispersibility of nano-boron nitride in the polytetrafluoroethylene system, effectively improving the wear resistance and adhesion of the wear-resistant layer, and improving the wear resistance of the fabric.
[0014] Preferably, the mass ratio of the nano-boron nitride to the polyimide is 1:(0.3-0.5).
[0015] By adopting the above technical solution, the mass ratio of nano-boron nitride and polyimide is controlled within the above range, which can effectively improve the dispersibility of nano-boron nitride.
[0016] Preferably, the wear-resistant agent also includes 5-7 parts of nano silicon nitride.
[0017] By adopting the above technical solution, nano silicon nitride has the properties of high hardness and high strength, can fill the gaps inside the wear-resistant layer, make the prepared wear-resistant layer denser, and at the same time improve the hardness of the wear-resistant layer.
[0018] In addition, nano silicon nitride can serve as a rigid support point, preferentially bearing loads and having a dispersion strengthening effect, while nano boron nitride acts as a solid lubricant and plays a role in protecting the coating. Therefore, nano silicon nitride and nano boron nitride are both added to the wear-resistant agent with polytetrafluoroethylene as the main raw material, so that the wear-resistant agent has a positive effect of one plus one being greater than two, thereby further improving the wear resistance of the wear-resistant agent, and further improving the wear resistance of the fabric.
[0019] Preferably, the nano silicon nitride is prepared by modification, and the modification preparation method of the nano silicon nitride comprises the following steps: S10, adding a silane coupling agent to a mixed solution of anhydrous ethanol and deionized water to prepare a silane coupling agent solution; S20, after activating the nano silicon nitride, add the silane coupling agent solution and stir thoroughly, then add acetic acid until the system is adjusted to pH = 7. After the reaction is complete, centrifuge with anhydrous ethanol until the upper liquid of the precipitate is neutral. Finally, take the upper liquid of the precipitate and dry it to obtain modified nano silicon nitride.
[0020] By adopting the above technical scheme, nano silicon nitride is treated with a silane coupling agent so that the surface particles of the nano silicon nitride are attached with a thin film, thereby increasing the roughness of the nano silicon nitride. On the one hand, the gaps between the nano silicon nitride are increased, which helps to evenly disperse the nano silicon nitride in the wear-resistant layer. On the other hand, the contact area between the nano silicon nitride particles and the wear-resistant layer is increased, which is beneficial to the meshing of the fabric body and the wear-resistant layer, increases the bonding force, and can effectively improve the wear resistance of the wear-resistant coating, thereby improving the wear resistance of the fabric.
[0021] Preferably, the mass ratio of the nano silicon nitride to the silane coupling agent is 1:(0.6-0.8).
[0022] By adopting the above technical solution and controlling the mass ratio of nano silicon nitride to the silane coupling agent within the above range, the roughness of nano silicon nitride can be effectively improved.
[0023] Preferably, the silane coupling agent is KH-550.
[0024] Preferably, the wear-resistant agent further comprises 4-6 parts of fluorinated graphene.
[0025] By adopting the above technical solution, fluorinated graphene can adsorb more polytetrafluoroethylene molecular chains around it, thereby enhancing the rigidity of the polytetrafluoroethylene coating and restricting the movement of the polytetrafluoroethylene molecular chains, reducing the adhesion of the polytetrafluoroethylene molecular chains at the friction interface, and thus reducing the wear rate of the polytetrafluoroethylene coating.
[0026] In addition, the network structure of fluorinated graphene in the polytetrafluoroethylene matrix has a "sieve" function, which can effectively reduce the agglomeration of nano-boron nitride, thereby improving the dispersibility of nano-boron nitride.
[0027] In a second aspect, the present application provides a method for preparing a high-toughness tensile-resistant and wear-resistant fabric as in the first aspect, using the following technical solution: A high-toughness tensile wear-resistant fabric comprises the following steps: S1. Mix polytetrafluoroethylene and deionized water, stir evenly, then add nano boron nitride, alcohol ester twelve, organic polyether ester, and fluorine surfactant, stir evenly, and prepare a wear-resistant agent; S2. Polylactic acid fiber and bamboo fiber are mixed and woven to form a fabric body, a wear-resistant agent is coated on the surface of the fabric body, and then heated and cured to allow the wear-resistant agent to cure on the surface of the fabric body to form a wear-resistant layer, thereby preparing a high-toughness tensile and wear-resistant fabric.
[0028] In summary, the present application includes at least one of the following beneficial technical effects: 1. Adding nano boron nitride to the wear-resistant agent can, on the one hand, increase the gap of the wear-resistant coating and make the wear-resistant coating more dense. On the other hand, nano boron nitride has a good lubricating effect. At the same time, when the surface of the fabric produces wear resistance, nano boron nitride will form a dense transfer film on the surface of the fabric, thereby improving the wear resistance of the wear-resistant layer, and then improving the wear resistance of the fabric. In addition, nano boron nitride will directly increase the contact area with its extremely small particle size, and nano particles have good thixotropic properties, thereby improving the adhesion of the wear-resistant layer on the surface of the fabric body.
[0029] 2. Nano silicon nitride can be used as a rigid support point, bearing loads preferentially, and has the effect of dispersion strengthening, while nano boron nitride acts as a solid lubricant and plays the role of protective coating. Therefore, nano silicon nitride and nano boron nitride are added to the wear-resistant agent with polytetrafluoroethylene as the main raw material, so that the wear-resistant agent has a positive effect of one plus one being greater than two, thereby further enhancing the wear resistance of the wear-resistant agent and further improving the wear resistance of the fabric. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of the overall structure of a high-toughness, tensile-resistant and wear-resistant fabric in an embodiment of the present application.
[0031] Description of reference numerals: 1. Fabric body; 2. Wear-resistant layer. DETAILED DESCRIPTION
[0032] The following is combined with Figure 1 This application is described in further detail.
[0033] The present application embodiment discloses a high-toughness tensile and wear-resistant fabric. Figure 1 The fabric comprises a fabric body 1, which is woven from polylactic acid fiber and bamboo fiber. The fabric body 1 is covered with a wear-resistant layer 2, which is obtained by coating a wear-resistant agent on the surface of the fabric body 1.
[0034] The present application is further described in detail below in conjunction with the embodiments and comparative examples. The raw materials involved in the present application can all be obtained commercially, among which polylactic acid fiber is provided by Wuhan Kemik Biomedical Technology Co., Ltd., organic polyether ester is provided by Jilin Petrochemical Design Institute, polytetrafluoroethylene is provided by Shanghai Aladdin Biochemical Technology Co., Ltd., and polyimide is provided by Shanghai Xuerong Chemical Technology Co., Ltd.
[0035] Example 1 The anti-wear agent comprises the following components by weight: 45g of polytetrafluoroethylene, 9g of nano boron nitride, 2.1g of alcohol ester dodecahydrate, 1.5g of organic polyether ester, 0.7g of fluorine surfactant and 10g of deionized water.
[0036] The preparation method of high-toughness tensile wear-resistant fabric comprises the following steps: S1. After mixing polytetrafluoroethylene and deionized water, ultrasonically disperse the mixture for 5 minutes, and then add nano boron nitride, alcohol ester twelve, organic polyether ester, and fluorine surfactant and mechanically stir for 2 hours to obtain a wear-resistant agent; S2. Polylactic acid fiber and bamboo fiber are mixed and woven to form a fabric body, and a wear-resistant agent is coated on the surface of the fabric body. After heating and curing at 220° C., the wear-resistant agent is cured on the surface of the fabric body to form a wear-resistant layer, thereby preparing a high-toughness tensile and wear-resistant fabric.
[0037] The fluorinated surfactant is FC4430.
[0038] Example 2 The difference between Example 2 and Example 1 is that the boron nitride is prepared by modification, and the modification preparation method of boron nitride comprises the following steps: 10 g of boron nitride and 3 g of polyimide were mixed and stirred evenly to obtain modified boron nitride.
[0039] Example 3 The difference between Example 3 and Example 1 is that the boron nitride is prepared by modification, and the modification preparation method of boron nitride comprises the following steps: 10 g of boron nitride and 5 g of polyimide were mixed and stirred evenly to obtain modified boron nitride.
[0040] Example 4 The difference between Example 4 and Example 1 is that the boron nitride is prepared by modification, and the modification preparation method of boron nitride comprises the following steps: 10 g of boron nitride and 4 g of polyimide were mixed and stirred evenly to obtain modified boron nitride.
[0041] Example 5 The difference between Example 5 and Example 4 is that the mass ratio of boron nitride to polyimide is 1:0.1.
[0042] Example 6 The difference between Example 6 and Example 4 is that the mass ratio of boron nitride to polyimide is 1:0.7.
[0043] Example 7 The wear-resistant agent includes the following components by weight: 42g of polytetrafluoroethylene, 7g of nano-boron nitride, 5g of nano-silicon nitride, 1.4g of alcohol ester dodecahydrate, 1.2g of organic polyether ester, 0.6g of fluorine surfactant, and 8g of deionized water.
[0044] The preparation method of high-toughness tensile wear-resistant fabric comprises the following steps: S1. After mixing polytetrafluoroethylene and deionized water, ultrasonically disperse the mixture for 5 minutes, and then add nano-boron nitride, nano-silicon nitride, alcohol ester twelve, organic polyether ester, and fluorine surfactant and mechanically stir for 2 hours to obtain a wear-resistant agent; S2. Polylactic acid fiber and bamboo fiber are mixed and woven to form a fabric body, and a wear-resistant agent is coated on the surface of the fabric body. After heating and curing at 220° C., the wear-resistant agent is cured on the surface of the fabric body to form a wear-resistant layer, thereby preparing a high-toughness tensile and wear-resistant fabric.
[0045] The fluorinated surfactant is FC4430.
[0046] Example 8 The difference between Example 8 and Example 7 is that: The wear-resistant agent includes the following components by weight: 48g of polytetrafluoroethylene, 11g of nano boron nitride, 7g of nano silicon nitride, 2.8g of alcohol ester dodecanedione, 1.8g of organic polyether ester, 0.7g of fluorine surfactant and 12g of deionized water.
[0047] Example 9 The difference between Example 9 and Example 7 is that: The wear-resistant agent comprises the following components by weight: 45g of polytetrafluoroethylene, 9g of nano boron nitride, 6g of nano silicon nitride, 2.1g of alcohol ester dodecahydrate, 1.5g of organic polyether ester, 0.7g of fluorine surfactant and 10g of deionized water.
[0048] Example 10 The difference between Example 10 and Example 9 is that the nano silicon nitride is prepared by modification, and the modification preparation method of the nano silicon nitride comprises the following steps: S10, adding 6 g of silane coupling agent to a mixed solution of 10 g of anhydrous ethanol and 40 g of deionized water to prepare a silane coupling agent solution; S20. Activate 10 g of nano silicon nitride in a vacuum drying oven at 120°C for 2.5 h, add silane coupling agent solution and stir ultrasonically for 20 min, then add acetic acid until the system is adjusted to pH = 7, react at 70°C for 6 h, and then centrifuge with anhydrous ethanol until the upper layer of the precipitate is neutral. Finally, take the upper layer of the precipitate and put it into a vacuum drying oven at 60°C for 24 h to obtain modified nano silicon nitride.
[0049] The silane coupling agent is KH-550.
[0050] Embodiment 11 The difference between Example 11 and Example 9 is that the nano silicon nitride is prepared by modification, and the modification preparation method of the nano silicon nitride comprises the following steps: S10, adding 8 g of a silane coupling agent to a mixed solution of 10 g of anhydrous ethanol and 40 g of deionized water to prepare a silane coupling agent solution; S20. Activate 10 g of nano silicon nitride in a vacuum drying oven at 120°C for 2.5 h, add silane coupling agent solution and stir ultrasonically for 20 min, then add acetic acid until the system is adjusted to pH = 7, react at 70°C for 6 h, and then centrifuge with anhydrous ethanol until the upper layer of the precipitate is neutral. Finally, take the upper layer of the precipitate and put it into a vacuum drying oven at 60°C for 24 h to obtain modified nano silicon nitride.
[0051] The silane coupling agent is KH-550.
[0052] Example 12 The difference between Example 12 and Example 9 is that the nano silicon nitride is prepared by modification, and the modification preparation method of the nano silicon nitride comprises the following steps: S10, adding 7 g of a silane coupling agent to a mixed solution of 10 g of anhydrous ethanol and 40 g of deionized water to prepare a silane coupling agent solution; S20. Activate 10 g of nano silicon nitride in a vacuum drying oven at 120°C for 2.5 h, add silane coupling agent solution and stir ultrasonically for 20 min, then add acetic acid until the system is adjusted to pH = 7, react at 70°C for 6 h, and then centrifuge with anhydrous ethanol until the upper layer of the precipitate is neutral. Finally, take the upper layer of the precipitate and put it into a vacuum drying oven at 60°C for 24 h to obtain modified nano silicon nitride.
[0053] The silane coupling agent is KH-550.
[0054] Embodiment 13 The difference between Example 13 and Example 12 is that the mass ratio of nano silicon nitride to silane coupling agent is 1:0.5.
[0055] Embodiment 14 The difference between Example 14 and Example 12 is that the mass ratio of nano silicon nitride to silane coupling agent is 1:0.9.
[0056] Embodiment 15 The difference between Example 15 and Example 12 is that the anti-wear agent further includes 4 g of fluorinated graphene.
[0057] That is, the wear-resistant agent includes the following components by weight: 45g of polytetrafluoroethylene, 9g of nano-boron nitride, 6g of nano-silicon nitride, 4g of fluorinated graphene, 2.1g of alcohol ester twelve, 1.5g of organic polyether ester, 0.7g of fluorine surfactant, and 10g of deionized water.
[0058] Example 16 The difference between Example 16 and Example 15 is that the anti-wear agent further includes 6 g of fluorinated graphene.
[0059] Embodiment 17 The difference between Example 17 and Example 15 is that the anti-wear agent further includes 5 g of fluorinated graphene.
[0060] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the anti-wear agent does not contain nano boron nitride.
[0061] Performance Testing The fabrics prepared in Examples 1-17 and Comparative Example 1 were subjected to performance tests, as follows: With reference to GB / T21196-2007 "Determination of the abrasion resistance of fabrics by the Martindale method", under standard three-level atmospheric pressure, a YG401 flat grinder was used, with a pressure weight of 250g, 240 grains / cm2 sandpaper, and 300 revolutions. An analytical balance was used to weigh the mass before and after grinding, and the mass loss rate was calculated. The test results are recorded in Table 1.
[0062] Table 1 Data analysis Specifically combining the test results of Examples 2-4 and Example 1, the wear resistance of Examples 2-4 is better than that of Example 1. The analysis is as follows: the difference between Examples 2-4 and Example 1 is that the nano-boron nitride is modified by polyimide to improve the dispersibility of the nano-boron nitride, thereby improving the positive effect of adding nano-boron nitride to the wear-resistant agent to improve the wear resistance, thereby improving the wear resistance of the fabric.
[0063] Specifically combining the test results of Examples 7-9 and Example 4, the wear resistance of Examples 7-9 is better than that of Example 4. The analysis is as follows: the difference between Examples 7-9 and Example 4 is that: nano silicon nitride is also added to the wear-resistant agent. On the one hand, nano boron nitride can improve the wear resistance of the wear-resistant agent. On the other hand, nano silicon nitride and nano boron nitride are both added to the wear-resistant agent, so that the wear-resistant agent has a positive effect of one plus one being greater than two, thereby further improving the wear resistance of the wear-resistant agent, and then further improving the wear resistance of the fabric.
[0064] Specifically combining the test results of Examples 10-12 and Example 9, the wear resistance of Examples 10-12 is better than that of Example 9. The analysis is as follows: the difference between Examples 10-12 and Example 9 is that the nano-silicon nitride is modified by a silane coupling agent to improve the dispersibility of the nano-silicon nitride, thereby improving the positive effect of adding nano-silicon nitride to the wear-resistant agent to improve the wear resistance, thereby improving the wear resistance of the fabric.
[0065] Specifically combining the test results of Examples 15-17 and Example 12, the wear resistance of Examples 15-17 is better than that of Example 12. The analysis is as follows: the difference between Examples 15-17 and Example 12 is that: fluorinated graphene is also added to the wear-resistant agent, which on the one hand reduces the adhesion of the polytetrafluoroethylene molecular chain at the friction interface and reduces the wear rate of the polytetrafluoroethylene coating; on the other hand, it improves the dispersibility of nano-boron nitride, thereby improving the wear resistance of the wear-resistant agent and further improving the wear resistance of the fabric.
[0066] Specifically combining the test results of Example 1 and Comparative Example 1, the wear resistance of Example 1 is better than that of Comparative Example 1. The analysis is as follows: the difference between Example 1 and Comparative Example 1 is that nano boron nitride is added to the wear-resistant agent, and the nano boron nitride will form a dense transfer film on the surface of the fabric, thereby improving the wear resistance of the wear-resistant agent, and then improving the wear resistance of the fabric.
[0067] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A high-toughness, tensile-resistant and wear-resistant fabric, comprising a fabric body (1), wherein the fabric body (1) is woven from polylactic acid fibers and bamboo fibers, and is characterized in that: The surface of the fabric body (1) is covered with a wear-resistant layer (2), and the wear-resistant layer (2) is obtained by coating a wear-resistant agent on the surface of the fabric body (1), and the wear-resistant agent comprises 42-48 parts of polytetrafluoroethylene, 7-11 parts of nano boron nitride, 1.4-2.8 parts of alcohol ester dodecanedione, 1.2-1.8 parts of organic polyether ester, 0.6-0.8 parts of fluorine surfactant, and 8-12 parts of deionized water.
2. The high-toughness tensile and wear-resistant fabric according to claim 1, characterized in that: The nano boron nitride is prepared by modification, and the modification preparation method of the nano boron nitride comprises the following steps: The nano boron nitride and polyimide are mixed and stirred evenly to obtain modified boron nitride.
3. The high-toughness tensile and wear-resistant fabric according to claim 2, characterized in that: The mass ratio of the nano boron nitride to the polyimide is 1:(0.3-0.5).
4. The high-toughness tensile and wear-resistant fabric according to claim 2, characterized in that: The wear-resistant agent also includes 5-7 parts of nano silicon nitride.
5. The high-toughness tensile-resistant and wear-resistant fabric according to claim 4, characterized in that: The nano silicon nitride is prepared by modification, and the modification preparation method of the nano silicon nitride comprises the following steps: S10, adding a silane coupling agent to a mixed solution of anhydrous ethanol and deionized water to prepare a silane coupling agent solution; S20, after activating the nano silicon nitride, add the silane coupling agent solution and stir thoroughly, then add acetic acid until the system is adjusted to pH=7. After the reaction is complete, centrifuge with anhydrous ethanol until the upper liquid of the precipitate is neutral. Finally, take the upper liquid of the precipitate and dry it to obtain modified nano silicon nitride.
6. The high-toughness tensile-resistant and wear-resistant fabric according to claim 5, characterized in that: The mass ratio of the nano silicon nitride to the silane coupling agent is 1:(0.6-0.8).
7. The high-toughness tensile and wear-resistant fabric according to claim 5, characterized in that: The silane coupling agent is KH-550.
8. The high-toughness tensile and wear-resistant fabric according to claim 5, characterized in that: The wear-resistant agent also includes 4-6 parts of fluorinated graphene.
9. A method for preparing the high-toughness tensile wear-resistant fabric as claimed in claim 1, comprising the following steps: S1. Mix polytetrafluoroethylene and deionized water, stir evenly, then add nano boron nitride, alcohol ester twelve, organic polyether ester, and fluorine surfactant, stir evenly, and prepare a wear-resistant agent; S2. Polylactic acid fiber and bamboo fiber are mixed and woven to form a fabric body, a wear-resistant agent is coated on the surface of the fabric body, and then heated and cured to allow the wear-resistant agent to cure on the surface of the fabric body to form a wear-resistant layer, thereby preparing a high-toughness tensile and wear-resistant fabric.